ANALYSIS OF FACTORS AFFECTING FIRM VALUE - Anissa Nurul Rokhimah; Nia Tresnawaty; Meyfida Ilyas (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study aims to examine the effect of capital structure, profitability, and firm size on firm value in companies belonging to the basic materials sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research seeks to provide empirical evidence regarding which financial factors contribute significantly to firm value creation. The population of this research consists of all basic materials sector companies listed on the IDX during the observation period. Using purposive sampling based on predetermined criteria, 103 valid observations were obtained. The study employs secondary data sourced from the IDX and applies multiple linear regression analysis as the analytical method. The results show that capital structure has no significant effect on firm value, while profitability and firm size both have significant positive effects on firm value. This indicates that firm value in the basic materials sector is primarily influenced by the company’s ability to generate profits and maintain larger business scale. This study provides new insights into the financial determinants of firm value within the Indonesian basic materials sector, specifically during the post-pandemic recovery period (2021–2024). The findings emphasize the relative insignificance of capital structure compared to profitability and firm size, which enriches the literature on corporate finance in emerging markets